Roles of TLR7 in Schistosoma japonicum Infection-Induced Hepatic Pathological Changes in C57BL/6 Mice - Feng, Yuanfa; Xie, Hongyan; Shi, Feihu; Chen, Dianhui; Xie, Anqi; Li, Jiajie; Fang, Chao; Wei, Haixia; Huang, He; Pan, Xingfei; Tang, Xiaoping; Huang, Jun (Frontiers in Cellular and Infection Microbiology, 2021)
S. japonicum infection can induce granulomatous inflammation in the liver of the host. Granulomatous inflammation limits the spread of infection and plays a role in host protection. Toll-like receptor 7 (TLR7) is an endosomal TLR that recognizes single-stranded RNA (ssRNA). In this study, the role of TLR7 in S. japonicum infection-induced hepatitis was investigated in both normal and TLR7 knockout (KO) C57BL/6 mice. The results indicated that TLR7 KO could aggravate S. japonicum infection-induced damage in the body, with less granuloma formation in the tissue, lower WBCs in blood, and decreased ALT and AST in the serum. Then, the expression of TLR7 was detected in isolated hepatic lymphocytes. The results indicated that the percentage of TLR7+ cells was increased in the infected mice. Hepatic macrophages, DCs, and B cells could express TLR7, and most of the TLR7-expressing cells in the liver of infected mice were macrophages. The percentage of TLR7-expressing macrophages was also increased after infection. Moreover, macrophages, T cells, and B cells showed significant changes in the counts, activation-associated molecule expression, and cytokine secretion between S. japonicum-infected WT and TLR7 KO mice. Altogether, this study indicated that TLR7 could delay the progression of S. japonicum infection-induced hepatitis mainly through macrophages. DCs, B cells, and T cells were involved in the TLR7-mediated immune response.